A Contested Freedom of Religion or Belief (FoRB) under the Majority Power: The Dynamics of Shia Community in Indonesia - Suheri, Suheri (LP2M - Universitas Islam Negeri Walisongo Semarang, 2024)
The concept of Islamic law in Indonesia is dynamic, dominating several sectors but often arising with controversial effects. One of the minority groups affected is the Shi'a Islam. From the government, the MUI (Indonesian Ulama Council) and